A Translation Analysis On Verb Phrase In Divergent Novel By Anggun Prameswari - Arlita, Sylvia Indah, Dr. Dwi Haryanti, M.Hum, Nur Hidayat, M.Pd (2015)
The research paper analysisEnglishverb phrase inDivergentnovel. The study aims (1) at identifyingtranslation variations of Englishverb phrase found in Divergentnovel and (2) atdescribing the accuracy translation of English verb phrase found in Divergent novel. The type of this research is descriptive qualitative research. The object of the study is thenovel entitled Divergentand its translation. The data of this study is English verb phrase found in Divergentnovel. Data source used in this research are the documentation of the data research paper and the informants. The researcher uses document, and questionnaire, in collecting data. The data are analyzed by using comparing method. Based on the analysis, there are 9 types of English verb phrase. They are verb phrase translated into Indonesian verb consists of 159 or 2,97% data, 1 or 0,2% data Englishverb phrase translated into Indonesiannoun, 13 or 2,4% data Englishverb phrase translated into Indonesian adjective, 11 or 2% data English verb phrase translated into Indonesian adverb, 32 or 6% data English verb phrase translated into Indonesian adjective phrase, 16 or 3% data English verb phrase translated into Indonesian adverb phrase, 4 or 0,7% data English verb phrase translated into Indonesian noun phrase, 270 or 50,4% English verb phrase translated into Indonesian verb phrase, and 30 or 5,6% deletion. In their accuracy, from 1124English modal verb there are 174 data or 15,5% accurate, 902 data or 80,2% less accurate and 48 data or 4,3% not accurate. It can be concluded that from 1124 data English verb phrase translation variations are accurate.